2021
DOI: 10.1111/jfr3.12699
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of flood adaptation: Parametric and semiparametric assessment

Abstract: Flood adaptation measures are indispensable to offset agricultural losses emanating from the increasing frequency and intensity of floods. Therefore, it is necessary to identify key precursors of adaptation for the success of flood‐related adaptation programs. Using cross‐sectional household survey data from rice farmers of eastern Nepal, this study explores existing adaptation practices along with the factors influencing farmers' adaptation strategies. Both parametric and semiparametric forms of the binary ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
(96 reference statements)
1
6
0
Order By: Relevance
“…In addition, farmers living in char-lands with higher distances from the village center appear to have comparatively more proximity to the river in the char-lands, which may also influence their adaptation behavior. Flood experience has a significant influence on the adoption of flood adaptation strategies by both CBO participants and non-participants, which is consistent with other results [59,63]. Previous flood experience was associated with increased risk perception and flood preparedness, and individuals who had experienced floods had stronger feelings about future floods and stronger intentions to take adaptation measures than those who had not [54].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, farmers living in char-lands with higher distances from the village center appear to have comparatively more proximity to the river in the char-lands, which may also influence their adaptation behavior. Flood experience has a significant influence on the adoption of flood adaptation strategies by both CBO participants and non-participants, which is consistent with other results [59,63]. Previous flood experience was associated with increased risk perception and flood preparedness, and individuals who had experienced floods had stronger feelings about future floods and stronger intentions to take adaptation measures than those who had not [54].…”
Section: Discussionsupporting
confidence: 87%
“…Since displacement is motivated by socioeconomic factors (Brasington 2021), we also considered adaptation ability, determined by finances, experience, and education (Adger and Vincent 2005) as control variables. Rogers et al (2020) and Pathak (2021) examine the impact of economic viability on possible adaptation solutions, and some researchers have confirmed that flood experience influences adaptation mechanisms Budhathoki, Paton, Lassa, Bhatta, and Zander 2020;Ullah et al 2020). Because this study was based on property-level adaptation and data regarding education were unavailable, we agreed that economic and income factors would be more appropriate (Hudson, Bubeck, and Thieken 2021) than education.…”
Section: Data and Variablesmentioning
confidence: 91%
“…It is crucial to limit exposure and vulnerability and reduce sources of flood hazard to increase adaptation 19 . Flood adaptation refers to a group of actions that make existing socioeconomic and ecological systems stronger in the face of flooding impacts 20 . Adaptation measures should also tackle developmental needs to increase the adaptive capacity of vulnerable communities 21 .…”
Section: Literature Reviewmentioning
confidence: 99%